Determination of Serum Infliximab Concentration by Point-of-care Devices in Children With Inflammatory Bowel Disease. Issue 4 (October 2019) - Curci, Debora; Lucafò, Marianna; Cifù, Adriana; Bramuzzo, Matteo; Martelossi, Stefano; Favretto, Diego; De Pellegrin, Francesca; Fabris, Martina; Vascotto, Fulvia; Naviglio, Samuele; Ventura, Alessandro; Stocco, Gabriele; et al.
ABSTRACT: Objectives: Therapeutic drug monitoring is becoming increasingly important in clinical decision-making in children with inflammatory bowel disease (IBD). However, enzyme-linked immunosorbent assay (ELISA) assays do not allow results to be provided in real-time. We sought to compare 2 point-of-care (POC) devices for quantification of serum infliximab concentration with 2 validated ELISA assays in children with IBD. Methods: We studied 32 serum samples from 19 children with IBD treated with infliximab. Serum samples were collected immediately before drug infusion (trough level). Infliximab was measured using 2 POC infliximab assays, Quantum Blue (POC IFX/QB) and Rida Quick (POC IFX/RQ), and 2 ELISA assays: Lisa-Tracker (used as primary reference), and Promonitor (used as second control). Intraclass correlation coefficient (ICC) was assessed for quantitative comparison. Qualitative analysis was also performed to evaluate whether POC assays would correctly classify infliximab serum according to a target window (between 3 and 7 μg/mL). Results: ICC was 0.82 and 0.87 for POC IFX/QB and POC IFX/RQ with the primary reference ELISA assay, respectively; ICC between the 2 ELISA assays was 0.87. Classification of results according to therapeutic intervals showed good agreement between pairs of assays, with kappa of 0.67 and 0.80 for POC IFX/QB and POC IFX/RQ, respectively, with reference ELISA, and 0.81 between the 2 ELISAs. Accuracy of POC assays was better for drug levels <3 μg/mL. Conclusions: POC infliximab assays showed good agreement with traditional ELISA assays. POC devices may represent a viable option for real-time therapeutic drug monitoring in children treated with infliximab.